Observed Energy Use by Broiler and Pullet Farms - Aaron P. Turner; John P. Chastain; Hunter F. Massey (AgriEngineering)
Evaluating farm-scale energy used for broiler production can provide insight into how these facilities use energy and allow for seasonal and managerial influences to be evaluated. This study evaluated farm-scale energy consumption for South Carolina broiler production using energy records from 17 broiler and 4 pullet farms. Monthly electric use showed low to moderate correlation (r ranging from 0.476–0.630) with ambient temperature but had limited predictive usefulness. There was no clear pattern in monthly electrical energy use for broiler barns. However, pullet barns were more consistent and could be grouped into seasons. No significant differences (p < 0.05) in annual electric or gas use were observed between farms with generally better equipment and otherwise similar farms, but production type did influence annual electric use. The average annual electrical use was 23.6 kWh m−2 for farms producing larger birds, 8.7 kWh m−2 for those producing smaller birds, and 17.0 kWh m−2 for pullet farms. Electrical energy use accounted for 37% of total energy in broiler barns and 32% of energy in pullet barns. Combined electric and gas consumption averaged 214 MJ m−2 yr−1 across all farms. These findings help better quantify farm-scale energy used for broiler production and provide benchmark values for energy use.